PENCAK SILAT SEBAGAI MEDIA DAKWAH: (Analisis Pada Perguruan Pencak Silat Susun Sirih Kecamatan Selakau) - Dagun; Deni Irawan; A.Rafik (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2021)
This research was conducted to explain that Pencak Silat is one of the martial arts sports that can be used as a medium for preaching especially at the Susun Sirih Pencak Silat College, Selakau District. The objectives of this study were: 1) To determine the forms of preaching media in the Susun Sirih Pencak Silat College, Selakau District. 2) To find out the application or the process of delivering da'wah messages at the Susun Sirih Pencak Silat College, Selakau District. This research uses a descriptive approach with a qualitative type. The data sources used are primary and secondary. The results of this study are; 1) There are two forms of preaching media in the Selakau Subdistrict Pencak Silat College, namely: pledge and discourse which have an important role to act as an intermediary for delivering da'wah messages. 2) the application or process of delivering da’wah messages at the Susun Sirih Pencak Silat College, Selakau District, in the application process using verbal communication and non-verbal communication, this is intended so that the recipient of the da'wah message can properly receive the message conveyed.